Triboelectric spray ionization. (26th January 2013) - Özdemir, Abdil; Lin, Jung‐Lee; Gillig, Kent J.; Chen, Chung‐Hsuan
Abstract : Triboelectric spray ionization (TESI) is a variation of electrospray ionization (ESI) using common instrumental components, including gas flow, solvent flow rate and heat, the only difference being the use of a high‐voltage power supply for ESI or a static charge for TESI. The ionization of solvent or analyte is due to the electrostatic potential difference formed between the spray electrode and counter electrode. The ion source contains a pneumatic spray operated over a range of flow rates (0.15–1.5 µl/min) and gas pressures (0–100). This new design contains a standalone spray assembly and an optional metal mesh in front of the spray. There are several parameters that affect the performance during ionization of molecules including the flow rate of solvent, gas pressure, temperature, solvent acidity, distance and potential difference between emitter and counter electrode. A variable electrostatic potential can be applied for higher ionization efficiency. The new ionization method was successfully applied to solutions of various proteins under different conditions. The same charge‐state distributions compared to other ESI techniques are observed for all the protein samples. The unique feature of TESI is very efficient spraying by using a natural electrostatic potential even at the potential that a human body can produce. This provides very gentle ionization efficiency of peptides and proteins in different solvents. Copyright © 2013 John Wiley & Sons, Ltd.